Characterization of the shape memory effect in polymers - Na, Hsi-Chung (2014)
This report discusses about shape memory polymers, and the techniques used to characterize their shape memory effect. The materials that this report will focus on are VeroWhitePlus Polymerized Resin and Polyimide. Wax and Sponge experiments were also conducted to demonstrate certain shape memory mechanisms.